2013
DOI: 10.2207/qjjws.31.1s
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Behavior Metal Vapor during Gas Tungsten Arc Welding

Abstract: This study shows the time variation of temperature distribution and concentration distribution of metal vapor during gas tungsten arc welding. In this study, stationary gas tungsten arc welding of pure iron was conducted in helium as shielding gas. We investigated the influence of iron vapor on arc plasma and mechanism of iron vapor transportation from the weld pool into the arc plasma. We observed the arc plasma two-dimensionally with spectrometric method. We captured three different monochromatic images simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Past studies have reported visualization of metal vapor derived from the anode in TIG welding. 17,18) The luminescence intensity of the line spectrum depends on the number density and the temperature and is expressed by Eq. (1).…”
Section: High-speed Visualization Of Metal Vapormentioning
confidence: 99%
“…Past studies have reported visualization of metal vapor derived from the anode in TIG welding. 17,18) The luminescence intensity of the line spectrum depends on the number density and the temperature and is expressed by Eq. (1).…”
Section: High-speed Visualization Of Metal Vapormentioning
confidence: 99%
“…There are past studies that have visualized anode-derived metal vapor in TIG welding. [17,18]. In this experiment, the relative intensity method was used for the observation of tungsten vapor.…”
Section: High-speed Visualization Of Metal Vapormentioning
confidence: 99%
“…In recent, the imaging technique based on high-speed camera observation with imaging monochromators or appropriate band-pass filters has been developed. Temperature distribution of free-burning arc during tungsten-inert gas arc welding process was successfully visualized (Nakanishi et al, 2013;Bachamann et al, 2013).…”
Section: Introductionmentioning
confidence: 99%